2009
DOI: 10.1080/10503300802702105
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative research interviews

Abstract: After presenting a brief overview of the complexity of the qualitative interviewing process used by psychotherapy researchers, the authors discuss some of the major ideas that psychotherapy researchers using such interviews must consider both before and during the interview process. They then offer thoughts regarding approaches to strengthen qualitative interviews themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(145 citation statements)
references
References 33 publications
2
137
0
6
Order By: Relevance
“…The means to access a subject's experiences range widely, from open-ended, unstructured approaches to highly structured protocols with preset questions. The open interview is a relatively unstructured approach applied in ethnography, grounded theory, and phenomenology that may use an evolving set of questions, such that later participants may respond to quite different queries from those put to earlier participants (Knox & Burkard, 2009). Sometimes only a first, topicintroducing question is asked and the remainder of the interview proceeds as a follow-up and expansion on the interviewee's answer to the first questions.…”
Section: Methodsmentioning
confidence: 99%
“…The means to access a subject's experiences range widely, from open-ended, unstructured approaches to highly structured protocols with preset questions. The open interview is a relatively unstructured approach applied in ethnography, grounded theory, and phenomenology that may use an evolving set of questions, such that later participants may respond to quite different queries from those put to earlier participants (Knox & Burkard, 2009). Sometimes only a first, topicintroducing question is asked and the remainder of the interview proceeds as a follow-up and expansion on the interviewee's answer to the first questions.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Kvale and Brinkmann (2009) and Knox and Burkard (2009) suggest interviewing as many individuals as necessary to reach saturation, while Guest, Bunce and Johnson (2006) found that saturation occurs within the first twelve interviews, with basic elements for common themes being present as early as after six interviews. Such assertions are supported by various publications that have gathered and analysed place branding interview data from five to eighteen participants (Bennett & Savani, 2003;Hankinson, 2001Hankinson, , 2005Hankinson, , 2009Park & Petrick, 2006;Stubbs, Warnaby & Medway, 2002 Responses to the questions were recorded, transcribed, and subsequently analysed using thematic analysis (Creswell, 1998).…”
Section: Stage 1: Approaches To Managing Place Brand Architecturesmentioning
confidence: 99%
“…A few officers came in predetermined to say very little and gave monosyllabic or vague answers, not an uncommon experience for researchers in terms of responses (Hutchinson and Wilson, 1992). It might be one of the techniques that interviewees adopt partly to manage their feelings of vulnerability (Knox and Burkard, 2009), especially if they felt that I was evaluating them (Adler and Adler, 2002). In a few other cases, I felt that their response denoted a sort of passive aggressive domination, almost as if they were adopting the stance, 'you might make me sit here, but you cannot make me talk'.…”
Section: Conducting Interviews: Power Negotiationsmentioning
confidence: 99%